2018
DOI: 10.1371/journal.pntd.0006968
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the rSh28GST urinary schistosomiasis vaccine: A phase 3 randomized, controlled trial in Senegalese children

Abstract: BackgroundUrinary schistosomiasis, the result of infection by Schistosoma haematobium (Sh), remains a major global health concern. A schistosome vaccine could represent a breakthrough in schistosomiasis control strategies, which are presently based on treatment with praziquantel (PZQ). We report the safety and efficacy of the vaccine candidate recombinant 28-kDa glutathione S-transferase of Sh (rSh28GST) designated as Bilhvax, in a phase 3 trial conducted in Senegal.Methods and findingsAfter clearance of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 30 publications
3
80
0
Order By: Relevance
“…The P28GST protein was produced as a recombinant protein (rSh28GST) from Saccharomyces cerevisiae cultures (TGY73.4-pTG8889 strain). The manufacturing process was conducted according to good manufacturing practice (GMP) guidelines, by Eurogentec S.A. (Seraing, Belgium), as described previously [7]. The rSh28GST clinical batch (M-BIX-P03/225a) was lyophilized under GMP conditions by Miltenyi (Bergisch Gladbach, Germany), with 225 µg (±10%) per vial.…”
Section: Experimental Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The P28GST protein was produced as a recombinant protein (rSh28GST) from Saccharomyces cerevisiae cultures (TGY73.4-pTG8889 strain). The manufacturing process was conducted according to good manufacturing practice (GMP) guidelines, by Eurogentec S.A. (Seraing, Belgium), as described previously [7]. The rSh28GST clinical batch (M-BIX-P03/225a) was lyophilized under GMP conditions by Miltenyi (Bergisch Gladbach, Germany), with 225 µg (±10%) per vial.…”
Section: Experimental Treatmentmentioning
confidence: 99%
“…The causal relationships between AEs and P28GST treatment were established according to the method of Bégaud et al [10], and classified as follows: not related, possibly related, probably related, and certainly related. SAEs that were suspected to be related to P28GST treatment, but never previously described, were called suspected, unexpected serious adverse reactions (SUSARs) [6,7]. Safety outcomes were assessed at baseline (pre-inclusion visit), at inclusion, and at months 1, 2, 3, 4, 6, 9, and 12.…”
Section: Safety Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase 1 human clinical trial showed that rSh28GST adsorbed to Alhydrogel induced a Th2-dependent immune response in immunized healthy subjects and was well tolerated [37]. The same authors also reported that the co-administration of rSh28GST and PZQ was also well tolerated in healthy volunteers during a Phase 2 clinical trial [38]. However, in a recent phase 3 trial design to investigate the safety, immunogenicity and efficacy of rSh28GST in infected children, no sufficient efficacy was observed.…”
Section: Schistosoma Haematobium 28-kd Glutathione Stransferasementioning
confidence: 99%
“…However, in a recent phase 3 trial design to investigate the safety, immunogenicity and efficacy of rSh28GST in infected children, no sufficient efficacy was observed. Some of the reasons suggested by the authors for lack of efficacy were possible counter effects of repeated PZQ administration and vaccine regimen geared towards blocking IgG4 production rather than induction of protective IgG3 antibodies [38].…”
Section: Schistosoma Haematobium 28-kd Glutathione Stransferasementioning
confidence: 99%